ОСОБЕННОСТИ ЛОКАЛЬНЫХ УСИЛЕНИЙ ЭЛЕКТРИЧЕСКОГО ПОЛЯ ПРОВОДЯЩИМИ ВКЛЮЧЕНИЯМИ В НЕЛИНЕЙНОЙ ПОЛИМЕРНОЙ ИЗОЛЯЦИИ - Щерба, М.А. (Інститут електродинаміки НАН України, Київ, 2015)
The features of the mathematical modeling and analysis of the electric field (EF) distortion in the polyethylene insulation near the water micro-inclusions and micro-treeing taking into account its non-linear characteristics were studied. It was taken into consideration that the insulation interlayer polarization in a strong EF on the boundary with water micro-defects can cause volume charge accumulation that is sufficient for increase the field strength to values under which the dielectric permittivity and specific conductivity of insulation change in several orders, and they are the functions of EF strength. The regularities of changes of the maximal value of low-frequency sinusoidal EF strength and the total current density in polyethylene insulation depending on the characteristic sizes and shapes of its water inclusions have been studied as well as the results were compared with similar calculations in linear dielectrics. References 13, figures 2, tables 2.